Multidimensional Heterogeneous Medical Data Push in Intelligent Cloud Collaborative Management System - Gang Liu; Xiaofeng Li (Complexity)
The medical data in the intelligent cloud collaborative management system have multidimensional heterogeneous interference, and there are problems such as low data information update rate and poor push results in the push process. Therefore, a method for multidimensional heterogeneous medical data push was proposed. First of all, the logical architecture of the multidimensional heterogeneous data push system was determined, and the data push function was designed; secondly, redundant data removal and noise reduction preprocessing were conducted against the push data, correlation rules were used to integrate multidimensional heterogeneous medical data, the weight of medical data was calculated, the heterogeneous data matrix was constructed, and the integrated medical data were weighted to eliminate multidimensional heterogeneous interference. The results show that the data update rate of the proposed method is faster, the user retention and communication rate are high, the data push precision rate is over 80%, and the recall rate is as high as 76%. Therefore, its performance is significantly better than traditional methods.